Ovarian cycle of southern brown howler monkey (Alouatta guariba clamitans) through fecal progestin measurement - Silvestre, Thiago; Zanetti, Eveline S. [UNESP]; Duarte, Jose M. B. [UNESP]; Barriento, Fernando G.; Hirano, Zelinda M. B.; Souza, Julio C.; Passos, Fernando C. (Springer, 2017)
The ovarian cycle in howler monkeys (genus Alouatta) has beean investigated through several biological parameters (ranging between 16.3 and 29.5 days); however, no data exist concerning the ovarian activity of the southern brown howler monkey (Alouatta guariba clamitans). This study aimed to describe the ovarian cycle of A. g. clamitans by profiling fecal progestin concentrations. Over 20 weeks, fecal samples of eight captive adult females of A. g. clamitans were collected. The collections were made at dawn, 5 days a week, and the samples were frozen immediately following collection. Next, they were dried, pulverized and hormonal metabolites were extracted to determine progestin concentrations by enzyme immunoassay. Of the 758 samples tested, the mean concentration of fecal progestins was 2866.40 +/- 470.03 ng/g of dry feces, while the mean concentration at baseline was 814.47 +/- 164.36 ng/g of dry feces. Among the eight females, one showed no ovarian cyclicity and three presented periods of probable absence of cyclicity and low progestin concentrations. A mean duration of 16 +/- 0.52 days was observed for the 35 cycles studied. The interluteal phase lasted 4 +/- 0.37 days on average, with a mean concentration of fecal progestins of 467.98 +/- 29.12 ng/g of dry feces, while the luteal phase lasted 11 +/- 0.50 days, with a mean concentration of 4283.27 +/- 193.31 ng/g of dry feces. Besides describing the characteristics of the ovarian cycle, possible causes for the low concentrations of fecal progestins and periods of absence of cyclicity are also discussed.
Keywords: Howler; Fecal progestins; Reproduction; Noninvasive method; Ovulatory period